The transcendental imagination of other possible worlds - MOLINA VELÁSQUEZ, Carlos (Utopía y Praxis Latinoamericana, 2022)
In this paper, Franz Hinkelammert's critique of utopian reason is used, particularly his notion of "transcendental imaginations", to show the theoretical challenges that must be considered when thinking about other possible worlds, a fundamental problem for all praxis of emancipation. These challenges not only refer to the use of fantasy or the impossibility of alternative projects, but also to the limits of language, the preeminence of reality over “empiricism” and the adoption of a particular notion of “concrete universality”.